Use of the immunoglobulin G avidity assay to differentiate between recent Zika and past dengue virus infections. (4th April 2019) - Furuya, Andrea K.M.; Hunt, Danielle; George, Kirsten St.; Dupuis, Alan P.; Kramer, Laura D.; Shi, Pei-Yong; Wong, Susan
Abstract : Zika (ZIKV) and dengue (DENV) virus infections elicit a robust but cross-reactive antibody response against the viral envelope protein, while antibody responses against non-structural proteins (NS) are more virus specific. Building on this premise, we have previously developed a flavivirus multiplex microsphere immunoassay (MIA) for the serologic diagnosis of ZIKV and DENV infections. This assay significantly improved diagnostic accuracy; however, MIA could not differentiate more recent from past infections, which still represents a major diagnostic challenge. Therefore, an immunoglobulin G (IgG) based avidity assay was developed and its diagnostic performance evaluated. Specimens from New York State residents were submitted to the Wadsworth Center New York State Department of Health (NYSDOH) for routine clinical testing by Zika IgM ELISA and plaque reduction neutralization test (PRNT). Using our previously developed flavivirus MIA as a platform, we developed an IgG avidity assay to discriminate recent ZIKV from past DENV infections. Zika IgM positive specimens had an average Zika IgG avidity index of 14.8% (95% CI: 11.0–18.4%), while Zika IgM negative but flavivirus MIA and PRNT positive samples had an average Zika IgG avidity index of 34.9% (95% CI: 31.1–38.7%). Specimens positive for dengue antibodies by flavivirus MIA and PRNT had an average dengue IgG avidity index of 68.7% (95% CI: 62.7–75.0%). The IgG avidity assay accurately distinguished recent ZIKV from past DENV infections in patients who traveled to dengue endemic regions. This assay could be very useful in patients with high risk of Zika complications such as pregnant women and monitoring immune responses in vaccine trials.